A segurança alimentar frente OGM e transgênico: problemas jurídicos - Garcia, Ana Carolina de Morais (2018)
This work analyzes the use of biotechnological cultivars, their environmental, socioeconomic and, above all, the right to food and human health. They aim to show the contraposition between the social right to healthy food and GMO / transgenic risks, as well as legal guarantees for food safety, through the precautionary principle in European Community legislation, and to compare it with the principle of precaution in Brazilian legislation. It questions the precautionary principle, questioning whether this is a sufficient assumption to ensure food safety and health guaranteed by European and Brazilian community standards. It analyzes the use and consumption of genetically modified organisms and transgenics as barriers to the right to healthy food and environmental conservation. The research is bibliographical and documentary. The methodological path covers the analysis of theoretical contents, as well as relevant legislation and data from scientific institutions. In order to achieve this aim, a case-by-case study of European Community law, Case C-111/16 of the Court of Justice of the European Union concerning the planting of MON 810 maize in Italy, is being studied. The work is divided into the following chapters: in chapter 1 the historical contextualization of the agroindustrial complex and agriculture as an industry are discussed. Chapter 2 examines the conceptual, theoretical and normative notes of biotechnological cultivars. Chapter 3 analyzes European Community law and analyzes Case C-111/16 related to the planting of transgenic maize MON 810.